Systemic and Brain Pharmacokinetics of Milnacipran in Mice: Comparison of Intraperitoneal and Intravenous Administration - Sounak Bagchi; Ehsan Nozohouri; Yeseul Ahn; Dhavalkumar Patel; Ulrich Bickel; Vardan T. Karamyan (MDPI AG, 2023)
Milnacipran is a dual serotonin and norepinephrine reuptake inhibitor, clinically used for the treatment of major depression or fibromyalgia. Currently, there are no studies reporting the pharmacokinetics (PK) of milnacipran after intraperitoneal (IP) injection, despite this being the primary administration route in numerous experimental studies using the drug. Therefore, the present study was designed to investigate the PK profile of IP-administered milnacipran in mice and compare it to the intravenous (IV) route. First a liquid chromatography-mass spectrometry (LC-MS/MS) method was developed and validated to accurately quantify milnacipran in biological samples. The method was used to quantify milnacipran in blood and brain samples collected at various time-points post-administration. Non-compartmental and PK analyses were employed to determine key PK parameters. The maximum concentration (Cmax) of the drug in plasma was at 5 min after IP administration, whereas in the brain, it was at 60 min for both routes of administration. Curiously, the majority of PK parameters were similar irrespective of the administration route, and the bioavailability was 92.5% after the IP injection. These findings provide insight into milnacipran's absorption, distribution, and elimination characteristics in mice after IP administration for the first time and should be valuable for future pharmacological studies.